Planning the diffusion of a neck-injury prevention programme among community rugby union coaches - Donaldson, A.; Poulos, R. G. (British Journal of Sports Medicine, 2014)
Background: This paper describes the development of a theory-informed and evidence-informed, context-specific diffusion plan for the Mayday Safety Procedure (MSP) among community rugby coaches in regional New South Wales, Australia. Methods: Step 5 of Intervention Mapping was used to plan strategies to enhance MSP adoption and implementation. Results: Coaches were identified as the primary MSP adopters and implementers within a system including administrators, players and referees. A local advisory group was established to ensure context relevance. Performance objectives (eg, attend MSP training for coaches) and determinants of adoption and implementation behaviour (eg, knowledge, beliefs, skills and environment) were identified, informed by Social Cognitive Theory. Adoption and implementation matrices were developed and change-objectives for coaches were identified (eg, skills to deliver MSP training to players). Finally, intervention methods and specific strategies (eg, coach education, social marketing and policy and by-law development) were identified based on advisory group member experience, evidence of effective coach safety behaviour-change interventions and Diffusion of Innovations theory. Conclusions: This is the first published example of a systematic approach to plan injury prevention programme diffusion in community sports. The key strengths of this approach were an effective researcher-practitioner partnership; actively engaging local sports administrators; targeting specific behaviour determinants, informed by theory and evidence; and taking context-related practical strengths and constraints into consideration. The major challenges were the time involved in using a systematic diffusion planning approach for the first time; and finding a planning language that was acceptable and meaningful to researchers and practitioners.